Colonial Itineraries of Contemporary Mexico : Literary and Cultural Inquiries - Nogar, Anna M.; Estrada, Oswaldo (The University of Arizona Press, 2014)
"This book discusses rewritings of the Mexican colonia to question present-day realities of marginality and inequality, imposed political domination, and hybrid subjectivities. Critics examine literature and films produced in and around Mexico since 2000 to broaden our understanding beyond the theories of the new historical novel and upend the notion of the novel as the sole re-creative genre"--